Review article: Comparison of cosmetic regulatory policies in various countries toward consumer protection - Silvia, Deli; Putri, Kintan Amelia Asmoro; Segita, Nur Elisa; Nuryadin, Raissa Nuraini; Saputra, Rio Dimas; Nur, Yasmin Lutfiah (Universitas Ahmad Dahlan, 2024)
Cosmetics are various products that enhance physical appearance and care for the skin, hair, and body. Cosmetic regulation refers to the rules and regulations imposed by a country's government or health regulatory agencies to regulate the production, marketing, and use of cosmetic products. The purpose of writing this journal is to compare the regulation of cosmetic products in Indonesia with the regulation of cosmetic products abroad, and it is hoped that people will be more aware and understand the regulation of cosmetic products that have been established. The literature method is used to conduct a review article, and the criteria chosen are based on the originality and relevance of the reading. The result of this writing is that the requirements regarding labeling in various countries are similar, such as composition, country of manufacture, product name, instructions for use, full name and address of the owner of the notification number (manufacturer), manufacturing batch number, expiration date, and special precautions that must be considered when using. Consumers must consider different regulations for cosmetic products in each country. These must be considered when making or selling cosmetic products: import and export regulations, limited ingredients, and safety testing of cosmetic products. Keywords: Cosmetics, Export, Import, Labelling, Regulation